Strategi Pemasaran UMKM di Era Digital: Studi Kasus Penggunaan TikTok Shop oleh Sylviea Collection - Rizqiani, Nur Laili; Sadali, Ayatullah; Taufiq Abadi, Muhammad (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This research examines the marketing strategies used by MSME players, focusing on Sylviea Collection's use of TikTok Shop as a case study. MSMEs in Indonesia face various challenges, including the COVID-19 pandemic bug and changes in consumer shopping behavior towards the digital economy. One of the efforts made by MSMEs is to utilize TikTok Shop to market their products. This study concludes that MSMEs can increase the appeal and effectiveness of their TikTok content by using high-quality smartphones, non-rational persuasive advertising techniques, and functional ads that provide clear product information. With the right marketing strategy, MSMEs can expand their market in the growing digital era.